THE PUBLIC SPACE QUALITY OF LEBIH BEACH GIANYAR: REVIEW OF SOCIAL AND ECONOMIC FUNCTION - Permanasuri, Ni Putu Diah Agustin (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2020)
Public space function such as a place for interaction people, social activity, and fulfil of economic needs and also recreation. Â Public space must be exist even at big city either small city. Public space quality based on impact of abration are physical and non physical aspect. Physical aspect including facility of the area, public space condition, and design. Non physical aspect including responsif aspect, democracy, meaningful and accesibility. Lebih beach as a public space located at Gianyar regency, has intetresting area for people around the beach and also another regency. At this beach, many activity is held, such as social, economic activity, family entertainmet and also fish culinary. At this time, there is many change of Lebih beach because the impact of abration. Decrease of sapce between land and shoreline. This research will explain how the change of Lebih beach based on economic and social function because both of them is the dominant activity at Lebih beach. This is a descriptive qualitative research, with direct interview with the people at beach. The result is quality aspect of social function are democracy and meaningful aspect, and economic aspect are democracy, meaningful and quality of area.